2011
DOI: 10.1152/japplphysiol.00945.2010
|View full text |Cite
|
Sign up to set email alerts
|

The promoting effect of pentadecapeptide BPC 157 on tendon healing involves tendon outgrowth, cell survival, and cell migration

Abstract: Pentadecapeptide BPC 157, composed of 15 amino acids, is a partial sequence of body protection compound (BPC) that is discovered in and isolated from human gastric juice. Experimentally it has been demonstrated to accelerate the healing of many different wounds, including transected rat Achilles tendon. This study was designed to investigate the potential mechanism of BPC 157 to enhance healing of injured tendon. The outgrowth of tendon fibroblasts from tendon explants cultured with or without BPC 157 was exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
103
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 28 publications
4
103
1
Order By: Relevance
“…In principle, BPC 157 endothelium protection/angiogenesis in ulcer healing [2,[54][55][56] follows Szabo's and Trier's demonstration of endothelium protection and angiogenesis in alcohol-stomach lesions [75]. However, whilst the Szabo's sponge-implantation with injected agents provides a suited environmental where their angiogenic potential could be tested [76], the BPC 157 angiogenesis was additionally tested in tissues that would be less healed, i.e., deep skin burns [27,28], transected major muscle [67], and particularly, in those tissues such as tendon or ligament [77][78][79] commonly thought to be hypovascular, hypocellular and hyponeural tissue where angiogenic potential (shift toward the left in presentation of new blood vessels) can be convincingly combined with the increased healing and rescuing of function [56] (of note, BPC 157 promotes the ex vivo outgrowth of tendon fibroblasts from tendon explants, cell survival under stress and the in vitro migration of tendon fibroblasts by the activation of the FAKpaxillin pathway [80]). What's more, the BPC 157 effect on blood vessels integrity was directly assessed and shown particularly in serosa of fully distended rat stomach: The vessels showed to become thin with distention and thereby disappeared, particularly with intragastrical alcohol, unless BPC 157 had been given [4].…”
Section: Mechanism Implicationsmentioning
confidence: 99%
“…In principle, BPC 157 endothelium protection/angiogenesis in ulcer healing [2,[54][55][56] follows Szabo's and Trier's demonstration of endothelium protection and angiogenesis in alcohol-stomach lesions [75]. However, whilst the Szabo's sponge-implantation with injected agents provides a suited environmental where their angiogenic potential could be tested [76], the BPC 157 angiogenesis was additionally tested in tissues that would be less healed, i.e., deep skin burns [27,28], transected major muscle [67], and particularly, in those tissues such as tendon or ligament [77][78][79] commonly thought to be hypovascular, hypocellular and hyponeural tissue where angiogenic potential (shift toward the left in presentation of new blood vessels) can be convincingly combined with the increased healing and rescuing of function [56] (of note, BPC 157 promotes the ex vivo outgrowth of tendon fibroblasts from tendon explants, cell survival under stress and the in vitro migration of tendon fibroblasts by the activation of the FAKpaxillin pathway [80]). What's more, the BPC 157 effect on blood vessels integrity was directly assessed and shown particularly in serosa of fully distended rat stomach: The vessels showed to become thin with distention and thereby disappeared, particularly with intragastrical alcohol, unless BPC 157 had been given [4].…”
Section: Mechanism Implicationsmentioning
confidence: 99%
“…As a result, a particular feedback-process for the simultaneous healing of different tissues was suggested, leading to both internal and external wound healing, anastomosis and fistulas[1-7]. Others correlated the BPC 157 beneficial effects with the activation of a cellular FAK-paxillin signaling pathway and, subsequently, demonstrated that BPC 157 dose- and time-dependently increased the expression of growth hormone receptor, Janus kinase 2, which belongs to the downstream signal pathway of growth hormone receptor and may interact with other molecular pathways[42-44]. …”
Section: Introductionmentioning
confidence: 99%
“…In a series of acute and chronic injury models, BPC 157 consistently promoted healing after severe injuries in various tissues that were unable to heal spontaneously (Cerovecki et al, 2010;Cesarec et al, 2013;Chang et al, 2011;Gjurasin et al, 2010;Hrelec et al, 2009;Keremi et al, 2009;Klicek et al, 2008;Krivic et al, 2006Krivic et al, , 2008Mikus et al, 2001;Novinscak et al, 2008;Pevec et al, 2010;Sebecic et al, 1999;Seiwerth et al, 1997;Sever et al, 2009;Sikiric et al, 2003;Staresinic et al, 2003Staresinic et al, , 2006Tudor et al, 2010;Vuksic et al, 2007). BPC 157 also heals hypovascular, hypocellular, and hyponeural tissues (Cerovecki et al, 2010;Chang et al, 2011;Gjurasin et al, 2010;Krivic et al, 2006Krivic et al, , 2008Staresinic et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the effects of BPC 157 alone in wound healing, without any carrier, suggest that they are attributed to its peptidergic activity (Cerovecki et al, 2010;Cesarec et al, 2013;Chang et al, 2011;Gjurasin et al, 2010;Hrelec et al, 2009;Keremi et al, 2009;Klicek et al, 2008;Krivic et al, 2006Krivic et al, , 2008Mikus et al, 2001;Novinscak et al, 2008;Pevec et al, 2010;Sebecic et al, 1999;Seiwerth et al, 1997;Sever et al, 2009;Sikiric et al, 2003;Staresinic et al, 2003Staresinic et al, , 2006Stupnisek et al, 2015;Tudor et al, 2010;Vuksic et al, 2007). Further, the effects of BPC 157 alone in wound healing, without any carrier, suggest that they are attributed to its peptidergic activity (Cerovecki et al, 2010;Cesarec et al, 2013;Chang et al, 2011;Gjurasin et al, 2010;Hrelec et al, 2009;Keremi et al, 2009;Klicek et al, 2008;Krivic et al, 2006Krivic et al, , 2008Mikus et al, 2001;Novinscak et al, 2008;Pevec et al, 2010;Sebecic et al, 1999;Seiwerth et al, 1997;Sever et al, 2009;Sikiric et al, 2003;Staresinic et al, 2003…”
Section: Introductionmentioning
confidence: 99%